ANALISIS MISKONSEPSI SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA BERSTANDAR PISA DENGAN MENGGUNAKAN CERTAINTY OF RESPONSE INDEX (CRI) - Ramadhan, Mustafa; Sunardi, Sunardi; Kurniati, Dian (Kadikma, 2017)
Abstract. This study aims to identify student misconception in solving PISA standard mathematic problems using CRI (Certainty of Responses Index), to describe and determine the percentage of forms of student misconception. The instrument used in this study is reasonable multiple choice test and interview guidelines. To answer the question, students are required to write the process in solving the question and choose the answer, besides the students are asked to put CRI value (0-5) based on their level of confidence in answering the question. A student can be declared to understand the concept, misconception and ignorance of the concept by comparing the answer with CRI value which is filled by the students, and the misconception form that occurred can be determined by checking the process in solving the question. Based on the research result, the misconception percentage on the aspect of the process of formulating the situation mathematically on PISA problem is 18, 25%, on the aspect of the process of using concept, fact, procedure and mathematic reasoning the misconception percentage is 7,76% and on the aspect of the process of interpreting, applying, and evaluating mathematic result, the misconception percentage is 13,8%. The misconception forms that occurred are 13,6% of translation misconception, 7,7% misconception of concept, 10,6% of misconception of strategy, 9,1% of systematical misconception, 4,5% of misconception sign.and 4,5% of misconception on calculation. Keyword: Misconception, Certainty of Response Index (CRI), PISA, Students’ Misconception